Four ECG left ventricular hypertrophy criteria and the risk of cardiovascular events and mortality in patients with vascular disease. Issue 9 (September 2018) - van Kleef, Monique E.A.M.; Visseren, Frank L.J.; Vernooij, Joris W.P.; Nathoe, Hendrik M.; Cramer, Maarten-Jan M.; Bemelmans, Remy H.H.; van der Graaf, Yolanda; Spiering, Wilko
Abstract : Objective: The relation between different electrocardiographic left ventricular hypertrophy (ECG-LVH) criteria and cardiovascular risk in patients with clinical manifest arterial disease is unclear. Therefore, we determined the association between four ECG-LVH criteria: Sokolow-Lyon, Cornell product, Cornell/strain index and Framingham criterion; and risk of cardiovascular events and mortality in this population. Methods: Risk of cardiovascular events was estimated in 6913 adult patients with clinical manifest arterial disease originating from the Secondary Manifestations of ARTerial disease (SMART) cohort. Cox proportional regression analysis was used to estimate the risk of the four ECG-LVH criteria and the primary composite outcome: myocardial infarction (MI), stroke or cardiovascular death; and secondary outcomes: MI, stroke and all-cause mortality; adjusted for confounders. Results: The highest prevalence of ECG-LVH was observed for Cornell product (10%) and Cornell/strain index (9%). All four ECG-LVH criteria were associated with an increased risk of the primary composite endpoint: Sokolow-Lyon (hazard ratio 1.37, 95% CI 1.13–1.66), Cornell product (hazard ratio 1.54, 95% CI 1.30–1.82), Cornell/strain index (hazard ratio 1.70, 95% CI 1.44–2.00) and Framingham criterion (hazard ratio 1.78, 95% CI 1.21–2.62). Cornell product, Cornell/strain index and Framingham criterion ECG-LVH were additionally associated with an elevated risk of secondary outcomes. Cardiovascular risk increased whenever two, or three or more ECG-LVH criteria were present concurrently. Conclusion: All four ECG-LVH criteria are associated with an increased risk of cardiovascular events. As Cornell/strain index is both highly prevalent and carries a high cardiovascular risk, this is likely the most relevant ECG-LVH criterion for clinical practice. Abstract : Supplemental Digital Content is available in the text